Beachgoer participation in prevention of marine litter: Using design for behavior change. (July 2019) - Portman, Michelle E.; Pasternak, Galia; Yotam, Yasmin; Nusbaum, Ron; Behar, David
Abstract: Much marine litter comes from land-based sources, with a significant amount coming from activities on bathing beaches. Thus, the overall focus of this exploratory research is to identify elements important for the design of beach infrastructure (i.e., trash cans (TCs)) to reduce littering behaviors. We base our investigation on principles of a relatively new approach, called Design for Sustainable Behavior. In doing so, we consider design for two user groups: bathing beachgoers and beach managers. We examined these users' perceptions of beach TCs through the use of an on-line survey of beachgoers, in-depth interviews with Israeli beach managers, a survey of international Blue Flag beach managers and a design 'ideation' workshop. Most importantly, we found that there is interest on the part of beach managers and other stakeholders in applying design principles to improve TCs. The findings of this study have implications for further interdisciplinary – and multidisciplinary – research on this topic. Highlights: Marine litter effects can be addressed by better design of beach infrastructure. Beach users' and managers' perceptions of trash cans and signage are presented. Beachgoers prefer inconspicuous cans, although obtrusive ones are most effective. Beach managers are interested in applying design principles to improve trash cans. Application of design for sustainable behavior to trash can design is suggested.